TAILORED TIMING, HASHTAGS, AND CONTENT: WHAT DRIVES INSTAGRAM ENGAGEMENT IN TOP ISLAMIC UNIVERSITIES IN INDONESIA? - Deni Adha Akbari; Eti Rochaeti; Mulyaning Wulan; Rito (Jurnal Penelitian Manajemen Terapan (PENATARAN), 2025)
This study explores Instagram engagement strategies adopted by the top five Muhammadiyah universities in Indonesia, focusing on how content type, posting time, and hashtag use influence interaction metrics. Utilizing a mixed-methods approach, data were collected through the Virol analytics platform to analyze engagement rates, follower growth, and post interactions. The study reveals that video content generates the highest engagement across all universities, particularly when posted in the late afternoon or evening. Specific and targeted hashtags were more effective than generic ones in boosting interaction. The research offers a novel contribution by systematically analyzing content engagement across comparable educational institutions using real-time analytics and strategic timing. This has not been previously explored in the Indonesian higher education context with this level of granularity. Practically, the findings provide actionable insights for university marketing teams seeking to optimize social media strategies. By aligning content with user behavior and platform trends, institutions can enhance community engagement and strengthen their digital presence. The study’s implications are particularly valuable for educational institutions aiming to foster meaningful connections with stakeholders through strategic digital communication.